2023
DOI: 10.1186/s12876-023-02715-5
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional pelvic ultrasound is a practical tool for the assessment of anal fistula

Abstract: Objective This study aims to investigate the diagnostic value of three-dimensional pelvic ultrasound in the preoperative assessment of anal fistula compared with findings of MRI and surgery. Methods A total of 67 patients (62 males) with suspected anal fistula were analyzed retrospectively. Preoperative three-dimensional pelvic ultrasound and magnetic resonance imaging were performed in all patients. The number of internal openings and the type of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…14 Recent studies have demonstrated that 3D-EAUS enables the accurate anatomical assessment of stula-in-ano, contributes to the formulation of clear and appropriate surgical treatment plans before operation, and reduces the risk of anal incontinence and recurrence. 15 Brillantino et al reported that the overall sensitivity and speci city of hydrogen peroxide-enhanced 3D-EAUS for the diagnosis of perianal sepsis were 98.3% and 91.3%, respectively. 16 Nevertheless, in many cases, both EAUS and HPUS may not detect highly restricted (suprasphincteric), subcutaneous, horseshoe-type, or small additional branching lesions.…”
Section: Discussionmentioning
confidence: 99%
“…14 Recent studies have demonstrated that 3D-EAUS enables the accurate anatomical assessment of stula-in-ano, contributes to the formulation of clear and appropriate surgical treatment plans before operation, and reduces the risk of anal incontinence and recurrence. 15 Brillantino et al reported that the overall sensitivity and speci city of hydrogen peroxide-enhanced 3D-EAUS for the diagnosis of perianal sepsis were 98.3% and 91.3%, respectively. 16 Nevertheless, in many cases, both EAUS and HPUS may not detect highly restricted (suprasphincteric), subcutaneous, horseshoe-type, or small additional branching lesions.…”
Section: Discussionmentioning
confidence: 99%
“…TPUS assessment of perianal lesions can be appropriately improved using 3D imaging [ 7 ]. TPUS has been introduced for anal sphincter anatomy on multiple planes and high-resolution imaging of the anal canal [ 17 ]. In our study, 3D-TPUS had 95% accuracy in detecting the type of perianal fistula, which was confirmed by the surgical findings.…”
Section: Discussionmentioning
confidence: 99%